Os dentes da engrenagem : o papel dos desembargadores do Rio Grande Do Sul nas incriminações por tráfico privilegiado - Hypolito, Laura Girardi (2023)
This thesis intends to understand how the judges of the State of Rio Grande do Sul apply the privilege represented in art. 33, paragraph 4 of Law 11.343/06, which constitutes the conduct of privileged trafficking and provides for a possibility of reducing imprisonment from one-sixth to two-thirds. For this, an analysis was carried out of 420 judgments referring to appeals filed at the Court of Justice of the State of Rio Grande do Sul and filed regarding the application of the privilege, referring to the year 2019. Of these 420 judgments, 144 correspond to the First Criminal Chamber , 155 to the Second Chamber and 121 to the Third. The methodology adopted for assessing the data was mixed, so that both the quantitative and qualitative methods of analysis were used. Regarding the research problem, it questions whether second-degree judges would be repeating the behavior of first-degree judges, acting as mere cogs in drug trafficking incriminations - that is, acting in a punitive manner and denying the right to benefit from privilege –, or in the second instance there is a rupture of these actions of the magistrates. To answer this question, five chapters were developed. The first deals with formal drug control models, from prohibitionism to recent forms of regulation of marijuana markets. The second presents a case study of the regulatory model of recreational cannabis in Canada, carried out during the Sandwich Doctorate at the University of Ottawa. The third introduces the criminal drug policy in Brazil from four main axes of analysis: historical construction, current legislation, impacts and international perspective. The fourth chapter addresses trends in Brazilian criminal control in the post-democratization period and the fifth presents empirical data and results from the field. With the purpose of highlighting the performance of the justices, the following variables were analyzed in each judgment: defense, whether private or by public defender; gender of the defendant; type of crime committed; co-authorship; weapon, in case of apprehension; police witness; ostensive policing; variety of seized drug; drug volume; filing of the appeal; granting of the appeal; 1st degree decision, whether it was maintained or changed; relationship between first and second degree arrests; relationship between the regimes for serving first and second degree sentences; issuance of release permit; privilege, if it has been applied; why not, in case it has not been applied and the reasons. As main results, it was found that despite the legislation determining four conditions for the recognition of privileged trafficking - being the primary defendant, with a good record, not dedicated to criminal activities and not a member of a criminal organization - the judges of the First and Second Chambers did use of twenty-five extralegal reasons for not granting the benefit of the privilege, while the Third Chamber used only six. In this sense, from the analysis of the variables, it was evident that the Third Criminal Chamber differed from the other two Chambers studied, evidencing the existence of internal disputes in the studied legal field. This, while the Third Chamber presented judgments that were much more focused on a more guaranteeing understanding of the law and the Criminal Procedure, by adopting a posture of respect for the rights and guarantees of the defendants, granting most of the defense's appeals, while the other two Chambers acted in such a way as to reiterate very punitive behaviors in relation to the demands of those investigated and which, in most cases, did not respect the legislation and compliance with Due Process of Law.